Crack propagation and scale effect of random fractured rock under compression-shear loading - Yifan Chen; Biyang Sheng; Shijie Xie; Rihong Cao; Yixian Wang; Yanlin Zhao; Hang Lin (Journal of Materials Research and Technology, 2023)
Fractures and rock blocks are the essential components of rock mass, random fractured rock is the general manifestation of fractured rock mass, which is particularly significant in scale effect. To facilitate the tests, most of the previous studies on fractured rock mass were conducted on regular fractured rocks, which is not conducive to fully revealing the mechanical properties and failure characteristics of fractured rock mass. In this paper, the random fractured rock samples were produced with rock-like materials to investigate the fracture propagation and scale effect under compression-shear condition. Specifically, the samples were loaded by controlling the compression-shear angle to study the mechanical responses. In the test, speckle changes on the samples surface were recorded in real time, and the evolution of strain field was analyzed by digital image processing technology. Then, the internal relations among compression-shear angle, fracture distribution and crack propagation were discussed. Meanwhile, the failure modes of the random fractured samples with different compression-shear angles were summarized to reveal the influence of compression-shear angle on failure mode. Combined with PFC2D, the random fractured rock models of different scales were established to explore the mechanical characteristic variation, and the representative elementary volume of shear modulus was finally determined.